The problem of the process of transmission in the Pentateuch - Rendtorff, Rolf (Journal for the study of the Old Testament. Supplement series, 1990)
Rolf Rendtorff is interested above all in the process by which the Pentateuch reached the form in which it now lies before us. He concludes that the classic Documentary Hypothesis has been tried in the fire and found wanting, and traces briefly the scholarly path that led him to this conclusion. His approach has been met with strong disagreement, cautious agreement, and, in some quarters, relief and readiness to look for other ways than that of the documentary hypothesis to explain the formation of the Pentateuch. It is certain, however, that scholars of the Pentateuch cannot ignore Re